The mayflies (Ephemeroptera), stoneflies (Plecoptera), and caddisflies (Trichoptera) of the South Platte River Basin of Colorado, Nebraska, and Wyoming - Heinold, Brian, author; Kondratieff, B. C. (Boris C.), advisor; Zuellig, Robert E., committee member; Cranshaw, Whitney, committee member; Loftis, Jim C., committee member (Colorado State University. Libraries, 2010)
Nearly 5,000 mayfly (Ephemeroptera), stonefly (Plecoptera), and caddisfly (Trichoptera) (EPT) species records collected from the South Platte River Basin (SPRB) were compiled from literature, field surveys, and institutional and personal collections. From this effort, a total of 291 species (69 mayflies, 66 stoneflies, 156 caddisflies) representing 35 families and 134 genera are reported from 1,208 unique collection locations. The EPT fauna of the foothills transition zone appears to be the most diverse and best characterized physiographic province of the SPRB. Four caddisflies are reported from Colorado for the first time; Asynarchus circopa (Ross and Merkley), Orthotrichia cristata Morton, Leptocerus americanus Banks, and Helicopsyche n. sp. The mayflies Ephemera compar (Hagen) and Ephemerella apopsis McCafferty are apparently endemic to the South Platte River Basin; however, both species have not been reported since their original collections in 1873 and 1974, respectively. The microcaddisfly Ochrotrichia susanae Flint and Herrmann and the winter stonefly, Capnia Arapahoe Nelson and Kondratieff are currently under emergency petition in Colorado under the U.S. Endangered Species Act. Many other species were represented by few records and require further investigation to better understand their distributions.
Department Head: Thomas Holtzer.